Financial Security Risk - Oleksyk, Piotr (Zagrożenia bezpieczeństwa finansowego podmiotu gospodarczego, 2010)
The efficient functioning of every economic entity depends heavily on the flow of information, both external and internal. The internal information system is the basis for strategic decisions such as investment, as well as current operational ones, often aimed at remedial measures. Accounting in the supervision of the business entity plays a key role, in fact provides a vast amount of very important information. The information derived from the accounting system is used by owners to monitor the implementation of plans for business development. Company’s financial stability should be defined as the ability to maintain liquidity and ability to cover losses and inherent risks associated with the activities of the reserves and equity. The concept of coverage is contingent upon the solvency behaviour of two basic conditions: the external and internal determinants of institutional financial situation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 144-150
Keywords: risk management; financial reporting; financial accounting